Complete subsite mapping of a "loopful" GH19 chitinase from rye seeds based on its crystal structure. Issue 16 (18th July 2013) - Ohnuma, Takayuki; Umemoto, Naoyuki; Kondo, Kaori; Numata, Tomoyuki; Fukamizo, Tamo
Abstract : Crystallographic analysis of a mutated form of "loopful" GH19 chitinase from rye seeds a double mutant RSC‐c, in which Glu67 and Trp72 are mutated to glutamine and alanine, respectively, (RSC‐c‐E67Q/W72A) in complex with chitin tetrasaccharide (GlcNAc)4 revealed that the entire substrate‐binding cleft was completely occupied with the sugar residues of two (GlcNAc)4 molecules. One (GlcNAc)4 molecule bound to subsites −4 to −1, while the other bound to subsites +1 to +4. Comparisons of the main chain conformation between liganded RSC‐c‐E67Q/W72A and unliganded wild type RSC‐c suggested domain motion essential for catalysis. This is the first report on the complete subsite mapping of GH19 chitinase. Abstract : Crystallographic analysis of GH‐19 chitinase‐(GlcNAc)4 complex revealed eight subsites. Crystal structures of liganded and unliganded forms of the enzyme suggested the domain motion. Among the eight subsites, the GlcNAc residues at +1, −1, and −2 are strongly recognized by the enzyme.